Pengembangan Media Boneka Jari Terhadap Keterampilan Berbicara Siswa Kelas IV SDN Saga VI Kabupaten Tangerang - Yolanda Nur Anjeli; Nur Latifah (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
This research and development aims to determine the steps to produce finger puppet media on the speaking skills of fourth grade students of SD Negeri Tangerang Regency and to determine the quality of finger puppet media based on validity and quality aspects in terms of the assessment of media expert validators, material experts, practical experts. and student response questionnaires. The development model used in this study uses the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The results of this research and development show the level of validity of media experts and material experts with very good criteria and an average score of 4,3.The quality level of the expert practitioners' assessment and student response questionnaires with very good criteria and an average score of 4,9